THERIOFAUNA OF THE KAZAKHSTAN PART OF THE IRTYSH RIVER BASIN (Eurasian Journal of Ecology, 2024)
The article presents the results of a review of literary data and personal observations, and an assessment of the level of study of mammals in the Irtysh River basin is provided. The aim of the work was to compile a list of mammals, analyze the species diversity, and evaluate the impact of anthropogenic and natural factors on the state of the fauna of the Irtysh. The research methodology included field observations in two model areas – in the Black (Cherniy) Irtysh and the Pavlodar Irtysh region. A list of species was prepared, and a characterization of the theriofauna of the research area was given. Eighty-seven species of mammals from 6 orders and 19 families inhabit the two regions, five of which are included in the Red Book of the Republic of Kazakhstan. The Jaccard similarity index for the studied territories was 0,62. Seven alien species are recorded here, three species – the tiger (Panthera tigris), red wolf (Cuon alpinus), and saiga (Saiga tatarica) – have disappeared from the Irtysh fauna; the European beaver (Castor fiber) continues to restore its historical range. The conducted study has high scientific and practical significance, contributes to understanding the state of biodiversity of this region, and emphasizes the need to develop measures for the conservation and sustainable use of mammals in the face of climate change and anthropogenic activities.Keywords: theriofauna, species composition, Black (Cherniy) Irtysh, Pavlodar Irtysh region, Republic of Kazakhstan.